Hemoglobin Concentration and Memory Development in Malawian Children Aged 12–15 Months (P10-093-19). (13th June 2019) - Bragg, Megan; Stewart, Christine; George, Matthews; Caswell, Bess; Iannotti, Lora; Lutter, Chessa; Maleta, Kenneth; Prado, Elizabeth
Abstract: Objectives: Multiple studies have found associations between hemoglobin concentration (Hb) and cognitive development in children under age 2 y, including development of language and motor skills; however, its association with early memory development is less well studied. Our objective was to assess whether hemoglobin concentration was associated with scores on a memory task in a sample of children aged 12–15 months in Malawi. Methods: This analysis includes a subset of children ( n  = 450) from an ongoing trial evaluating eggs during complementary feeding in 660 Malawian children. Hb was measured using the HemoCue 201 Analyser at baseline, when children were 6–9 months old, and at endline 6 months later. The elicited imitation test, a nonverbal measure of memory, was administered at endline. In the test, children were shown eight novel objects. After a period of spontaneous interaction, children were shown a two-action sequence for each object and asked to imitate it, either immediately or after a delay of 10 minutes. Children were scored on their ability to perform the actions in any order (total actions score, 0–16) and to complete the sequences correctly (total sequences score, 0–8). The association of Hb at each time point with total actions was examined using multiple linear regression and with total sequences, categorized (<2 or ≥2 sequences), using multiple logistic regression. Both models controlled for the spontaneous actions produced, baseline Home Observation for the Measurement of the Environment score, maternal education, maternal age, and household asset index, and endline child age and the Family Care Indicators score. Results: The mean (SD) Hb at baseline was 10.4 (1.6) g/dL and at endline was 11.1 (1.3) g/dL. The mean (SD) total actions score was 6.8 (3.5), and 52.7% of the children had a sequences score below two. Total actions score was not significantly associated with Hb at either time point (baseline: P  = 0.99; endline: P  = 0.15). Total sequences score <2 was also not associated with Hb (baseline: P  = 0.90, endline: P  = 0.14). Conclusions: Hemoglobin concentration at 6–9 and 12–15 months of age was not associated with memory development at 12–15 months in this sample of Malawian children. Funding Sources: The Bill and Melinda Gates Foundation; UC Davis Blum Center.